Stan & Ollie - Baird, Jon S., 1972-; Coogan, Steve; Reilly, John C., 1965-; Henderson, Shirley, 1965- (Culver City, California : Sony Pictures Home Entertainment, 2019)
Comedy duo Laurel & Hardy attempt to jump start their film careers when they embark on a theatre tour of post-war Britain.
Anamorphic wide screen 1.85:1.
Steve Coogan, John C. Reilly, Shirley Henderson, Stephanie Hyam, Danny Huston.
MPAA rating: Not rated.
Keywords: Laurel, Stan -- Drama; Hardy, Oliver, -- 1892-1957 -- Drama; Comedians -- Drama; Fiction films; Feature films; Biographical films; Comedy films